Aberrant P53 Expression and the Development of Gallbladder Carcinoma and Adenoma - Shen-Nien Wang; Shin-Chang Chung; Kun-Bow Tsai; Chee-Yin Chai; Wen-Tsun Chang; Kung-Kai Kuo; Jong-Shyone Chen; King-Teh Lee (Kaohsiung Journal of Medical Sciences, 2006)
Gallbladder carcinoma (GBC) is a highly lethal but relatively rare neoplasm of the digestive tract. The progression from gallbladder adenoma to carcinoma remains unclear. The p53 gene is the most frequently mutated tumor suppressor in human cancers. In this study, we analyzed the expression patterns of the p53 protein in 22 cases of GBC, 17 cases of precursor lesions (16 gallbladder adenomas and 1 cystadenoma), and 15 cases of normal epithelia using immunohistochemical analysis. The results were correlated with clinicopathologic characteristics. We found that p53 expression was significantly increased in 59.1% (13/22) of GBC cases and in 17.6% (3/17) of gallbladder adenoma cases (p = 0.009). There was no p53 expression in the 15 cases of normal epithelia, and a significant difference was shown between normal epithelium and GBC cases (p < 0.001). In addition, the expression pattern of p53 protein did not show any significant correlation with the histologic type and the differentiation grade of GBC. In conclusion, we suggest that the aberrant p53 expression may play a role in the occurrence of GBC.